Penyuluhan kesehatan melalui siaran radio tentang menjaga kesehatan balita di masa pandemi Covid-19 - Istichomah Istichomah; I Putu Juni Andika; Firmina Theresia Kora (Jurnal Pengabdian Harapan Ibu (JPHI), 2021)
After Covid-19 was declared a global pandemic problem, the government had an obligation to maintain survival, including toddlers. The case of Covid-19 in children under five and the mortality rate for children under five with Covid which is quite high compared to other countries, makes us have to continue to prevent it from spreading from various ages. Toddlers as candidates for the nation's next generation must have good health conditions, one of which is by maintaining the health of toddlers during the Covid-19 pandemic. Yogyakarta Stikes and Sonora radio held a health education through radio broadcasts which lasted approximately 2 hours. This counseling contains about how to prevent Covid-19 at the individual and family level, implementation of immunization, completeness of toddler nutrition, and referrals to health facilities. This lecture activity provides information to the public on how to maintain their health. Based on the evaluation of radio listeners, it is known that listeners are quite active in asking questions about the correct use of masks, as well as about the implementation of posyandu. It is hoped that from this counseling, public awareness will continue to increase, which is indicated by the behavior of the community in adhering to health protocols. Keywords : health education, radio, children, covid-19